Genome-Wide Analysis of MIKC C -Type MADS Box Genes in Grapevine - Díaz Riquelme, José (2009)
MIKCC-type MADS box genes encode transcription factors that play crucial roles in plant growth and development. Analysis of the grapevine (Vitis vinifera) genome revealed up to 38MIKCC-type genes.We report here a complete analysis of this gene family regarding their phylogenetic relationships with homologous genes identified in other sequenced dicot genomes, their genome location, and gene structure and expression. The grapevine genes cluster in 13 subfamilies with their Arabidopsis (Arabidopsis thaliana) and poplar (Populus trichocarpa) counterparts. The lack of recent whole genome duplications in grapevine allows assigning the gene diversification processes observed within each subfamily either to an ancestral polyploidization event predating the divergence of those three species or to later duplication events within each lineage. Expression profiles of MIKCC-type genes in vegetative and reproductive organs as well as during flower and tendril development show conserved expression domains for specific subfamilies but also reflect characteristic features of grapevine development. Expression analyses in latent buds and during flower development reveal common features previously described in other plant systems as well as possible new roles for members of some subfamilies during flowering transition. The analysis of MIKCC-type genes in grapevine helps in understanding the origin of gene diversification within each subfamily and provides the basis for functional analyses to uncover the role of these MADS box genes in grapevine development.